Penerapan Metode Interpolasi Polinom Lagrange untuk Prediksi Teh Kering di PTPN IV Regional 4 - Ika Dewini Samosir; Syamsyida Rozi (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2026)
This study is based on the importance of accurate dry tea production planning to support the sustainability of production activities in the plantation sector. Uncertainty in production volume often poses an obstacle to production management, necessitating a method capable of predicting production based on available historical data. The purpose of this study is to apply the Lagrange polynomial interpolation method in predicting dry tea production at PT Perkebunan Nusantara IV Regional 4 based on land area and production yield data. The Lagrange polynomial interpolation method is used to form a polynomial function that passes through a number of known data points so that it can be used to estimate production values under certain conditions. The data used in this study are land area and dry tea production data for a specific period. The results of this study indicate that the Lagrange polynomial interpolation method can be used to predict dry tea production and provide an overview of the relationship between land area and production yield. The application of this method is expected to support production planning and decision making at PT Perkebunan Nusantara IV Regional 4.